Factors Associated with Ecstasy Use in Students of Qazvin University of Medical Sciences - * L (MSc.); ** A (B.Sc); ** A (B.Sc); *** H (Ph.D) (Tehran University of Medical Sciences, 2009)
Background & Aim: Drug addiction, especially addiction to Ecstasy has ruinous effect on lives. Lack of knowledge is the most important cause of Ecstasy use among young adults. Research studies showed that students use these pills in order to get comfort and to overcome grieves. Addiction to ecstasy has been increased in Iran in recent years. This study was carried out to assess the factors associated to Ecstasy use in students of Qazvin University of Medical Sciences. Methods & Materials: In this cross-sectional study, we recruited 200 students using clustered, random sampling. Data collection tool was a structured valid and reliable questionnaire containing 28 questions in two sections. Data were analyzed using Student t-test, ANOVA and chi-square tests. Results: Results indicated that the prevalence of Ecstasy use was 1.5%. Prevalence of alcohol and cigarette use was 1.5% too. Mean score of knowledge on Ecstasy was 9.8% (SD=3.8). Knowledge of the female students was higher than the knowledge of male ones. About 86.7% of the students took Ecstasy in order to end grieve due to family problems. Most important associated factors to Ecstasy use were: positive attitude toward Ecstasy use, lack of knowledge (96.5%), peer pressure (96%), and lck of parents' attention to their young children (94.5%). Conclusion: Lack of knowledge about complications of addiction to Ecstasy is the most important factor leading to addiction among students. Living in places such as dormitories and rented houses, and lack of parents' control over their children can be important factors related to addiction of students to Ecstasy, as well.   Key words: Ecstasy, young adult, student